Ceftazidime/Avibactam in Ventilator-Associated Pneumonia Due to Difficult-to-Treat Non-Fermenter Gram-Negative Bacteria in COVID-19 Patients: A Case Series and Review of the Literature - Giulia Jole Burastero; Gabriella Orlando; Antonella Santoro; Marianna Menozzi; Erica Franceschini; Andrea Bedini; Adriana Cervo; Matteo Faltoni; Erica Bacca; Emanuela Biagioni; Irene Coloretti; Gabriele Melegari; et al. (MDPI AG, 2022)
Ventilator-associated pneumonia (VAP) in critically ill patients with COVID-19 represents a very huge global threat due to a higher incidence rate compared to non-COVID-19 patients and almost 50% of the 30-day mortality rate. Pseudomonas aeruginosa was the first pathogen involved but uncommon non-fermenter gram-negative organisms such as Burkholderia cepacea and Stenotrophomonas maltophilia have emerged as other potential etiological causes. Against carbapenem-resistant gram-negative microorganisms, Ceftazidime/avibactam (CZA) is considered a first-line option, even more so in case of a ceftolozane/tazobactam resistance or shortage. The aim of this report was to describe our experience with CZA in a case series of COVID-19 patients hospitalized in the ICU with VAP due to difficult-to-treat (DTT) P. aeruginosa, Burkholderia cepacea, and Stenotrophomonas maltophilia and to compare it with data published in the literature. A total of 23 patients were treated from February 2020 to March 2022: 19/23 (82%) VAPs were caused by Pseudomonas spp. (16/19 DTT), 2 by Burkholderia cepacea, and 6 by Stenotrophomonas maltophilia; 12/23 (52.1%) were polymicrobial. Septic shock was diagnosed in 65.2% of the patients and VAP occurred after a median of 29 days from ICU admission. CZA was prescribed as a combination regimen in 86% of the cases, with either fosfomycin or inhaled amikacin or cotrimoxazole. Microbiological eradication was achieved in 52.3% of the cases and the 30-day overall mortality rate was 14/23 (60.8%). Despite the high mortality of critically ill COVID-19 patients, CZA, especially in combination therapy, could represent a valid treatment option for VAP due to DTT non-fermenter gram-negative bacteria, including uncommon pathogens such as Burkholderia cepacea and Stenotrophomonas maltophilia.